2015
DOI: 10.1177/1362361315605973
|View full text |Cite
|
Sign up to set email alerts
|

Children with autism spectrum disorder have an exceptional explanatory drive

Abstract: An "explanatory drive" motivates children to explain ambiguity. Individuals with autism spectrum disorders are interested in how systems work, but it is unknown whether they have an explanatory drive. We presented children with and without autism spectrum disorder unsolvable problems in a physical and in a social context and evaluated problem-solving and explanation-seeking responses. In the physical context (but not the social context), the children with autism spectrum disorder showed a stronger explanatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Pattern seeking involves cognitive drive to find and confirm patterns in the external environment. This phenomenon is closely allied to systemizing, though it also involves higher explanatory drive in non-social problem-solving in autism (37), and higher, albeit imbalanced, intelligence (7), given that systemizing is not positively associated with intelligence [e.g., (38)]. Enhanced pattern seeking in autism is also manifest in, for example: (a) pursuits in highly-organized collecting and related aspects of systemizing and (b) the associations of the autism spectrum with interests and skills in STEM disciplines [e.g., (10,39)].…”
Section: Pattern Seekingmentioning
confidence: 99%
“…Pattern seeking involves cognitive drive to find and confirm patterns in the external environment. This phenomenon is closely allied to systemizing, though it also involves higher explanatory drive in non-social problem-solving in autism (37), and higher, albeit imbalanced, intelligence (7), given that systemizing is not positively associated with intelligence [e.g., (38)]. Enhanced pattern seeking in autism is also manifest in, for example: (a) pursuits in highly-organized collecting and related aspects of systemizing and (b) the associations of the autism spectrum with interests and skills in STEM disciplines [e.g., (10,39)].…”
Section: Pattern Seekingmentioning
confidence: 99%
“…Given that susceptibilities to cognitive biases are negatively associated with measures of intelligence, weakly though significantly (e.g., Teovanović et al, 2015 ), these findings suggest that this component of intelligence is enhanced in autism, at least in some contexts. More-deliberative decision making in autism may be associated, and underpinned, by enhanced explanatory drive to seek information in ambiguous circumstances, with regard to physical (rather than social) problems (Rutherford and Subiaul, 2015 ).…”
Section: Autism and The Correlates Of Intelligencementioning
confidence: 99%
“…The hyper-systemizing process can be informed by greater attention to detail ( Baron-Cohen et al, 2009 ; Brosnan et al, 2012 ). Rutherford and Subiaul’s (2016) study, which focuses on the motivational urge for systemizing, indicated that autistic children showed a stronger explanatory drive than non-autistic children. The authors use the term “explanatory drive” to explain an individual’s desire to explain ambiguity and to explain how systems work.…”
Section: Social Stories™mentioning
confidence: 99%